Valuation of Remaining Service Life of H-Beam Steel Structure in the Floating Cafe Bridge at PT. Medco E&P Malaka - Alfarezy, Rafie Maulana (Yayasan Kawanad, 2024)
Bridges are critical infrastructure requiring optimal structural resilience to ensure safety and operational sustainability. A major threat to steel bridge structures is corrosion, which reduces material thickness and may lead to structural failure if unaddressed. This study evaluates the remaining service life (Remaining Life Assessment, RLA) of the H-Beam steel structure in the Floating Cafe Bridge at PT Medco E&P Malaka by measuring corrosion rates using the Ultrasonic Thickness Gauge (UTG) method. Data were collected from 40 measurement points on the Top Flange, Bottom Flange, and Web Flange of the H-Beam. Analysis revealed that the Top Flange in the right zone exhibited the highest corrosion rate (0.66 mm/year), resulting in a remaining service life of only 9 years. In contrast, the Bottom Flange in the middle zone showed the lowest corrosion rate (0.06 mm/year), with a remaining service life of 205 years. The primary factor accelerating corrosion is the dry-wet cycle caused by humidity, rainfall, and solar drying. The right zone experienced higher corrosion rates due to elevated humidity and poor ventilation. To extend the bridge’s service life, mitigation strategies such as reapplying anti-corrosion coatings, conducting regular Non-Destructive Testing (NDT) inspections, cleaning salt deposits, and improving drainage systems are recommended. These measures will enhance structural reliability and minimize corrosion-related risks.